2019
DOI: 10.3906/sag-1807-173
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy of epiduroscopic adhesiolysis in Failed Back Surgery Syndrome

Abstract: Backgraund and Aim: We aimed to compare the results of the treatment of the patients with failed back surgery syndrome (FBSS) by mechanical lysis and steroid hylase injection via epiduroscopy due to their stabilization status and to detect the effect of pathological diagnostic markers on prognosis and ongoing tretment protocol. Methods: Eighty-two patients with FBSS symtoms were included. Two groups were composed as group I (stabilized) and group II (non-stabilized). All patients were evaluated using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Two articles were RCTs, 36,37 three were prospective‐, 38–40 and four were retrospective 41–44 observational studies. Together, they included 392 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two articles were RCTs, 36,37 three were prospective‐, 38–40 and four were retrospective 41–44 observational studies. Together, they included 392 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Follow‐up data at 3 months were used as 6‐month data, and at 6 months as 12‐month data if no further data were available. Using the NOS for observational studies, four were rated as good, 39,41,43,44 one as moderate, 42 and two as poor 38,40 (Table 2b). Poor quality was rated because patients were excluded from follow‐up based on outcome or due to incomplete reporting of data.…”
Section: Resultsmentioning
confidence: 99%
“…According to previous studies, the clinical or surgical outcomes of SELD were found to be favorable in various lumbar spine diseases [ 3 7 , 12 17 ]. In particular, several recent papers regarding the clinical outcome of SELD for disc herniation have reported that the clinical outcome was favorable as there was significant improvement in low back pain or radiating leg pain, patient satisfaction rate of more than 70%, and low rates of surgical failure or recurrence [ 8 , 18 – 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…After the United States Food and Drug Administration approval of epiduroscopy, the concept of SELD was developed, and the literatures reported the clinical outcomes of SELD in not only disc herniation but also in spinal stenosis, adhesion, chronic low back pain, failed back syndrome, and cystic lesions in the lumbosacral spine [7-15, 19, 20]. However, considering the principles of SELD, the distinctive difference from conventional procedures of drug injection or adhesiolysis like epidural neuroplasty is the effect of laser ablation on hydrated soft tissue [17][18][19][20][21]. In other words, whereas the function of drug delivery or adhesiolysis could create a transient effect as in other procedures, laser ablation of soft disc herniation could lead to the permanent effect of decompression [22][23][24].…”
Section: Discussionmentioning
confidence: 99%